2015
DOI: 10.12957/demetra.2015.15014
|View full text |Cite
|
Sign up to set email alerts
|

Perfil Clínico-Nutricional E Consumo Alimentar De Idosos Do Programa Terceira Idade, Ouro Preto-Mg

Abstract: Clinical-nutritional profile and dietary intake of participants of the Elderly Program, Ouro Preto-MGRealizou-se estudo transversal com 28 idosos de faixa etária ≥ 60 anos. Na análise antropométrica, foram aferidos peso, altura, perímetro da cintura e calculado o índice de massa corporal. Os dados bioquímicos analisados foram: colesterol total e frações, triglicerídeos e glicose. Investigou-se também a presença de diabetes e hipertensão. A avaliação do consumo alimentar foi realizada por questionário de frequê… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0
14

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 20 publications
(16 reference statements)
1
2
0
14
Order By: Relevance
“…According to the present data, most elderlies are overweight; these data are supported by a study conducted in the city of Vitória, state of Espírito Santo, Brazil which found that 65.2% of the researched elderlies were overweight/obese (21) . This reality presented should be considered seriously, because overweight and obesity have significant health consequences, in the sense that they are easily associated with cardiovascular diseases, musculoskeletal disorders, impaired mobility and function.…”
Section: Resultssupporting
confidence: 86%
“…According to the present data, most elderlies are overweight; these data are supported by a study conducted in the city of Vitória, state of Espírito Santo, Brazil which found that 65.2% of the researched elderlies were overweight/obese (21) . This reality presented should be considered seriously, because overweight and obesity have significant health consequences, in the sense that they are easily associated with cardiovascular diseases, musculoskeletal disorders, impaired mobility and function.…”
Section: Resultssupporting
confidence: 86%
“…Resultado semelhante ao obtido em outro estudo, 11 no qual foi constatada maior procura das mulheres (60,4%) pelos serviços oferecidos nos ESF do município de Viçosa-MG. Pesquisas realizadas em Ouro Preto-MG e João Pessoa-PB confirmam essa tendência, ao revelar a presença de 71,4% e 79,7%, respectivamente, de idosas. 12,13 Estudos correlacionam o predomínio da população feminina pela procura de atendimento devido à maior sensibilização das mulheres para a promoção da saúde, em decorrência da experiência na utilização dos serviços de saúde em outras fases da vida, como a realização do pré-natal, parto e puericultura. 14 Existem diferenças de atitude entre homens e mulheres em relação ao controle e tratamento das doenças, sendo que os homens são, geralmente, mais resistentes à procura por serviços de saúde.…”
Section: Discussionunclassified
“…These individuals also presented changes in the blood glucose profile (56.5%) and high blood pressure (82.0%). Food intake analysis found that 93.0% and 89.0% of older adults had high intakes of ultra-processed foods and high glycemic index foods, respectively [40]. Intake of these foods, which contain numerous ingredients and generally high contents of saturated fat, cholesterol, sugar, and sodium, is related to the development of obesity and chronic noncommunicable diseases [41].…”
Section: Discussionmentioning
confidence: 99%